Feto-Maternal Outcomes of Labouring Patients in Booked and Unbooked Patients: Feto-Maternal Outcomes of Laboring Patients - Ghafoor, Maria; Irum Qureshi, Qandeela; Soomro, Sawina; Shah, Faryal; Mughis, Amber; Maqsood, Zainab (Pakistan Journal of Health Sciences, 2022)
The main factor contributing to poor feto-maternal outcomes is lack of antenatal care and awareness among pregnant ladies for need of booking in hospitals for their delivery management. Up to 39% of all obstetric patients in underdeveloped countries are hospitalized due to complications of labor, and same is case with neonates. Objective: To determine the association between patient booking status and outcomes because high maternal morbidity and mortality rates are indicative of the poor state of health services. Methods: A total of 380 patients, 190 booked patients admitted in emergency and 190 unbooked patients with fetal and maternal problems were included. The demographic data of each patient were recorded to determine the fetomaternal outcomes. Results: Different causes of obstructed labour such as CPD (60.62%), malpresentation (17.98%), and malposition (23.34%) were recorded in patients. In booked patients, 9.47, 3.15, and 5.78% of wound infection, anaemia, and ruptured uterus were recorded, respectively, while 11.05, 4.73, and 6.84%, respectively in unbooked patients. Among booked patients, 80.52% had maternal complications while 95.26% of unbooked had complications. Fetomaternal is a disorder that can be avoided and is common in underdeveloped nations. The majority of patients were unscheduled patients who did not obtain adequate antenatal care and as a result, showed up late in advanced labour with obstructional symptoms. CPD was the most typical reason for labour obstruction. Conclusions: Puerperal pyrexia was the most frequent maternal consequence, followed by PPH and UTI. Birth asphyxia was the most frequent prenatal consequence, followed by neonatal infection.